Nesoglasje med zdravnikom in bolnikom med posvetom - Kersnik, Janko (Medicinski razgledi, 2003)
Communication with patients presents an important part of a physicians' work. The disagreements that appear during the consultation process, can affect quality of care. This is the reason why we have to detect the disagreements intime and react accordingly. With this paper we would like to present the definition and the impact of the disagreement on the doctor patient relationship. The ways of dealing with the disagreement are described. A briefoutline of an instrument for collecting and analysing disagreements DisCois given.
Keywords: Bolnik, sodelovanje; Physician-Patient Relations; Patient Compliance; Bolnik, sprejetje zdravstvene oskrbe; Bolniki, osip; Patient Acceptance Of Health Care; Zdravnik-bolnik, odnosi; Patient Dropouts; bolniki; zdravniki; sporazumevanje; nesoglasja